The Phonetic structures of (Aziz) Potiphar’s wife story in The Quran - Saad, Yasmin Abdullah; AL- Saidalani, Khadija Abdelaziz (Arab Journal for Sciences and Research Publishing, 2019)
This is a descriptive study of the structural composition of the story of the wife of al- Aziz, aimed at highlighting the significance of those structures and it’s different methods. At first, it tackles the study of the phonological structures as the initial window towards the analysis of the text, starting from the inventory of the sounds in the story, knowing the most and least mentioned in terms of their dual qualities as (loudness: whisper, strength: softness, elevation: lowering) and study its impact and correlation from the semantic angle of the story. The study also reveals the vocabulary’s homogeneous unity between sound and meaning, and how it relates to different story contexts. The qualities of the phonetic structure represent form rhythmic dimensions that carry the semantic depth of the meanings of the story, and it was formed out of 892 sounds.